Differentiated Typology of Sex Work and Implication for HIV Prevention Programs among Female Sex Workers in Nepal - Mishra, Shiva Raj; Neupane, Sanjeev Raj (Frontiers in Public Health, 2015)
Background: Sex work in exchange for kind and cash has long been practiced in Nepal. The HIV prevention program in Nepal is focused mainly on these two typologies of sex work. There might be more typologies of sex work beyond streets and establishments seeking research and programmatic attention. The objective of the study is to explore the differentiated typologies of sex work. Methods: This is a cross-sectional study conducted using a qualitative technique. Researchers carried out eight Focus Group Discussions with female sex workers (FSWs) (n = 50) in different places of Tanahu district. Data were analyzed using a deductive thematic analysis approach. Results: We identified a more differentiated typology of sex work. Private contact-based sex work and the covert sex work on the cruising areas along the major highways were common. Sex work has become easier to operate with the advent of new technologies such as cell phone. With limited role of facilitation by brokers and pimps, now FSWs are better off and have longer duration of relationship with clients. Soft prostitution was common, as FSWs complemented their income through sex work. Conclusion: The conventional mode of peer and outreach educational approach needs to be further strengthened and modified according to the changing typology of sex work. HIV testing sites need to be further expanded to cruising areas along the highways.